Covet [large type] - Garvis Graves, Tracey (Thorndike Press large print basic series., 2013)
When Claire's husband Chris is offered a position that will keep him away from home four nights a week, he dismisses Claire's concern that time apart could be the one thing their fragile union can't weather. Police officer Daniel Rush pulls Claire over during a routine traffic stop, and they run into each other again at the Fourth of July parade. It doesn't take long before Claire and Daniel are in way over their heads and skating close to the line that Claire has sworn she'll never cross.